SCIENCE NATURE VOL. 2(2), PP.90-127, June 2019 (PDF of FULL MAGAZINE) - science nature (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
This issue entitled as NEW MAN has 5 original papers from 3 different countries authors of Indonesia, Canada and Malaysia. The incredible things in this issue are about customary laws findings in Aru islands region of 804 small islands to improve local people life from coastal marine areas, and the discovery of new herbal medicine products based on Galoba (zingiberaceae fruits) Maluku called as Herbal Blessing which is better than former Love herbal invented from STIKES Halmahera. Another conceptual thought to expand the improvement of nanobattery research was about anti-crack and a bit elastic nanobattery system for future technology and multitasking applications.